Amphibious adaptations in a newly recognized amphibious fish: Terrestrial locomotion and the influences of body size and temperature. (29th February 2016) - Magellan, Kit
Abstract: Amphibious animals are adapted for both aquatic and terrestrial habitats. The conflicting requirements for dual habitats are perhaps most pronounced in the air‐breathing fishes, which represent an intermediate stage between the totally aquatic habitat and terrestrial colonization. A key requirement for amphibious fishes is terrestrial locomotion. The different densities and compositions of air and water impose constraints for efficient terrestrial locomotion that differ from those required for aquatic locomotion. I investigated terrestrial locomotion in a small South African fish, Galaxias 'nebula', by exposing 60 individual fish to air in specially designed raceways and quantifying movement type and occurrence as a function of availability of water, fish size and environmental temperature. Nebula showed a sustained undulating form of terrestrial locomotion characteristic of amphibious fishes and also a transient ballistic locomotion (jumps) typical of fully aquatic species. Terrestrial movement was influenced by fish size, with medium‐sized fish undertaking more jumps towards water, and fewer jumps away from water, than their smaller or larger conspecifics. In contrast, axial undulation was mainly influenced by temperature. However, there was no consistent pattern in temperature effects presumably because temperature is just one of a suit of environmental factors that may affect terrestrial locomotion. Nebula's amphibious adaptations allow it to cope with the unpredictability inherent in its natural environment.